Understanding School Violence in Colombia - Caballero-León, Laura Marcela (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The article presents a state of art of Colombian studies on school violence published from the country's education faculties. It offers a historical overview of the emergence of research on the issue of school violence from the national, Latin American, and global context, with a description of the trends and approaches that have predominated in the analysis of the problem, and a state of the debate that questions the process of theoretical construction of the concept of school violence. The period of inquiry spans from the 90s. Methodologically, the proposal was oriented to investigate the research on school violence carried out from the faculties of education that responds to the epistemological and political interest of the question about violence in school. In addition to constructing a balance of the state of the question, the article raises new research problems derived from knowledge about the intellectual production of a specific topic in the educational field. It is especially located in the question of the subjects and the constitution of subjectivities from what is said about the school, the students, and the violence. The article concludes that school violence became a problem from the political speech and from there it was located in the school. There is still an unresolved epistemological void around the concept of school violence. The distance between the concepts of violence and school united in the category of school violence may be generating important contradictions between educational designs for conflict resolution and educational strategies for peace at school.